Dynamics of Development of Cultural Processes (International Journal of Scientific Trends, 2026)
Cultural development is a dynamic and multifaceted process influenced by globalization, technological progress, social transformation, and intercultural interaction. In the contemporary world, cultural processes are evolving rapidly under the impact of digital communication, migration, economic integration, and the expansion of global media. This article examines the major contemporary trends in cultural development, including digitalization, globalization, cultural hybridization, preservation of national identity, and the growing role of cultural industries. The study highlights the relationship between culture and social progress while emphasizing the importance of balancing innovation with the preservation of traditional values. The article also discusses challenges related to cultural homogenization and the necessity of intercultural dialogue in modern society.